Recent Advances in Synthesis and Properties of Hybrid Halide Perovskites for Photovoltaics - Vidyasagar, C. C.; Muñoz Flores, Blanca M.; Jiménez Pérez, Víctor Manuel (2018)
Abstract The progress made by the scientiﬁc community in emerging photovoltaic technologies over the past two decades has been outstanding. Numerous methods have been developed for the preparation of hybrid organic– inorganic perovskite solar cells. The power conversion efﬁciency has been up to 14% by a one-step vacuum deposition technique. A serious concern is the toxicity of the materials. In this review, several methods aimed at resolving these problems to some extent have been compiled, including eco-friendly synthesis. Further efﬁciency enhancements are expected following optimization, and a better fundamental understanding of the internal electron charge transfer, electron–hole diffusion to the corresponding layers, ﬂexibility, and stability-dependent bandgaps is reported. This paper explores the green synthesis of organic–inorganic perovskites for industrialization. Concerning the above facts, a simple low-cost model called ‘‘dispersed photovoltaic cells’’ is presented. Keywords Perovskites Solar cells Organic–inorganic perovskites Synthetic routes Fluorescence